Preparation method and application of hard carbon negative electrode material and sodium ion battery

By pre-calcining, acid leaching and mixed calcining with phenolic resin, the problem of fast removal of heteroatoms in heat treatment of existing hard carbon materials was solved, and a hard carbon negative electrode material with excellent electrochemical properties was prepared , improving its purity and performance.

CN119390043APending Publication Date: 2025-02-07DONGGUAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411308865.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the long-term heat treatment of existing hard carbon materials, there are problems such as fast removal of heteroatoms and carbon atom rearrangement affecting electrochemical performance, resulting in poor performance in sodium ion batteries.

Method used

The biomass material is pre-calcined, acid-limmed, mixed with phenolic resin, calcined and dried to prepare a hard carbon negative electrode material with excellent electrochemical properties.

Benefits of technology

Through this method, the problem of incomplete separation caused by high temperature pyrolysis and low hard carbon purity caused by heteroatom doping is avoided, and the performance and purity of hard carbon negative electrode materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390043A_ABST
    Figure CN119390043A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a hard carbon negative electrode material and a sodium ion battery. According to the method, biomass such as palm is used as a raw material, and the hard carbon anode material is prepared through pre-carbonization, acid pickling and impurity removal, high-temperature carbonization and crushing and screening; an electron microscope research shows that the prepared hard carbon has a porous communicated network structure; x-ray diffraction and Raman spectrum analysis show that the carbonized material has a disordered structure and relatively large interlayer spacing; the electrochemical research shows that the lignin in the palm is pyrolyzed at 800 DEG C, the permeability is better, and the initial discharge and charge capacities of 400mAh / g and 300mAh / g can be provided; according to the invention, an effective hard carbon production technology capable of realizing industrial batch production is developed, the hard carbon negative electrode material is prepared from waste to palm, the problems that tar cannot be completely separated due to high-temperature pyrolysis and the purity of hard carbon is not high due to heteroatom doping are solved, and other useless groups are not introduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a preparation method and application of a hard carbon negative electrode material and a sodium ion battery. Background Art

[0002] Hard carbon materials have a wide range of applications in the field of sodium-ion batteries, and biomass hard carbon has attracted much attention due to its advantages of low cost, easy availability and renewable raw materials. In the field of sodium-ion batteries, biomass hard carbon materials are gradually becoming the focus of research due to their significant advantages of low cost, easy availability and renewable raw materials. This material not only enriches the choice of negative electrode materials for sodium-ion batteries, but also provides a new way to achieve green and sustainable energy storage.

[0003] Biomass hard carbon can be converted into hard carbon materials with unique physical and chemical properties through carbonization processes such as pyrolysis. Its microstructure contains abundant nanopores, micropores and mesopores. These pore structures provide a large number of active sites for the embedding of sodium ions and promote the penetration of electrolytes, thereby increasing the ion diffusion rate. At the same time, the graphite microcrystalline regions in the hard carbon coexist with the non-graphitized regions d, forming a "house-yard" structure that is conducive to the reversible embedding and de-embedding of sodium ions. This feature significantly improves the cycle stability and rate performance of the battery.

[0004] Hard carbon on the market has the advantages of low cost, large interlayer spacing, disordered structure, and porous connectivity. However, in long-term heat treatment, the main method used is to pyrolyze the material in an open space under the protection of an inert atmosphere, that is, to place the material in an open porcelain boat for pyrolysis. This will cause the heteroatoms to be removed at a faster rate, which will inevitably affect the rearrangement of carbon atoms, thereby further affecting its electrochemical performance as a negative electrode material for sodium-ion batteries.

[0005] Based on the defects of current hard carbon, it is necessary to improve it. Summary of the invention

[0006] In view of this, the present invention provides a preparation method and application of a hard carbon negative electrode material and a sodium ion battery to solve or at least partially solve the defects existing in the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0009] Precalcining the biomass material to obtain a precursor;

[0010] placing the precursor in an acid solution for acid leaching;

[0011] Phenolic resin is added to the product after acid leaching, calcined, washed with water, and dried to obtain a hard carbon negative electrode material.

[0012] Preferably, the biomass material includes at least one of palm shells, pollen, corn silk, peanut shells, and coconut shells.

[0013] Preferably, phenolic resin is added to the product after acid leaching, and calcination is specifically performed as follows:

[0014] adding phenolic resin to the acid-leached product to obtain a mixture;

[0015] The mixture is placed in a container and a porous aluminum plate is inserted into the mixture;

[0016] The container is placed in a calcining furnace, heated from room temperature to 1100-1220°C at 2-5°C / min, and kept at this temperature for 2-3 hours, and then cooled to room temperature at 1-2°C / min;

[0017] The mass of the phenolic resin is 2-8% of the mass of the product after acid leaching.

[0018] Preferably, placing the precursor in an acid solution for acid leaching is specifically as follows:

[0019] The precursor is crushed;

[0020] The crushed precursor is placed in an acid solution, heated to 45-55°C, stirred for 2-3 hours, aged for 2-3 hours, filtered to remove the supernatant, water is added to the precipitate for washing, and then sodium hydroxide is added to adjust the pH to neutral, and the solid product is filtered to obtain the product after acid leaching.

[0021] Preferably, pre-calcining the biomass material to obtain a precursor specifically comprises the following steps:

[0022] The biomass material is placed in a vacuum calcining furnace, calcined at 100-150°C for 30-50 minutes without oxygen, and then calcined at 180-250°C for 30-50 minutes without oxygen;

[0023] Inert gas is introduced into the vacuum calcining furnace, and the temperature is raised to 800-900°C, kept at this temperature for 1-2 hours, and cooled to room temperature to complete the pre-calcination.

[0024] Preferably, the biomass material is placed in a vacuum calcining furnace, heated from room temperature to 100-150°C at 1-2°C / min, and calcined for 30-50min without oxygen, and then heated to 180-250°C at 1-2°C / min and calcined for 30-50min without oxygen;

[0025] Inert gas is introduced into the vacuum calcining furnace, the temperature is raised to 800-900°C at 1-2°C / min, kept at this temperature for 1-2h, and cooled to room temperature at 1-2°C / min, thus completing the pre-calcination;

[0026] In the process of heating to 800-900°C at 1-2°C / min, the flow rate of the inert gas introduced is 30-60 mL / min; in the process of keeping the temperature for 1-2 hours, the flow rate of the inert gas introduced is 190-250 mL / min;

[0027] The inert gas includes at least one of nitrogen, helium, argon and neon.

[0028] Preferably, the mass concentration of the acid solution is 20-40%;

[0029] The acid solution includes at least one of a phosphoric acid solution, a sulfuric acid solution, and a nitric acid solution.

[0030] Preferably, phenolic resin is added to the product after acid leaching, calcined, washed with water, and dried to obtain the hard carbon negative electrode material:

[0031] The calcined product is added to water, heated to 45-55° C., stirred for 2-3 hours, filtered and dried to obtain a hard carbon negative electrode material.

[0032] In a second aspect, the present invention also provides an application of a hard carbon negative electrode material prepared by the preparation method in the preparation of a sodium ion battery.

[0033] In a third aspect, the present invention further provides a sodium ion battery, comprising the hard carbon negative electrode material prepared by the preparation method.

[0034] The preparation method and application of a hard carbon negative electrode material and a sodium ion battery of the present invention have the following beneficial effects compared with the prior art:

[0035] 1. The present invention uses lignin-rich biomass materials as raw materials, and pre-calcines, acid-leaches, mixes with phenolic resin, and then calcines and dries them. The auxiliary material is phenolic resin. During the calcination process, the lattice formation stage will not form a completely identical unit cell structure due to impurities or uneven calcination temperature. Therefore, the use of phenolic resin for filling provides phenolic groups while providing carbon chains, which can better fill the gaps in the hard carbon layer, thereby improving the performance of the hard carbon negative electrode material;

[0036] 2. The present invention uses biomass such as palm as raw material, and prepares hard carbon anode materials through pre-carbonization, acid washing and impurity removal, high-temperature carbonization, crushing and screening; electron microscopy studies show that the prepared hard carbon has a porous interconnected network structure; X-ray diffraction and Raman spectroscopy analysis show that the carbonized material has a disordered structure with a large interlayer spacing (0.37nm); electrochemical studies show that 800°C pyrolysis of lignin in palm has good permeability and can provide 420mAh / g and 360mAh / g initial discharge and charge capacities; the sepals of palm (biowaste) produce hard carbon materials at moderate carbonization temperatures, with optimal microstructural properties and large interlayer spacing. These properties are responsible for its good electrochemical properties as an anode material NIB. The present invention has developed a set of effective industrial batch hard carbon production technology, which is used to prepare hard carbon negative electrode materials from palm from waste garbage, avoiding the problem of high-temperature pyrolysis with tar problems that cannot be completely separated and the problem of low purity of hard carbon due to heteroatom doping, and will not introduce other useless groups. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 is the XRD spectrum of the hard carbon negative electrode material prepared in Example 1 of the present invention;

[0039] Figures 2 to 5 The SEM images of the hard carbon negative electrode material prepared in Example 1 at different magnifications;

[0040] Figure 6 The charge and discharge curves of a sodium ion battery assembled with the hard carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0041] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0044] The present invention provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0045] S1. Pre-calcining the biomass material to obtain a precursor;

[0046] S2, placing the precursor in an acid solution for acid leaching;

[0047] S3. Add phenolic resin to the product after acid leaching, calcine, wash with water, and dry to obtain a hard carbon negative electrode material.

[0048] The preparation method of the hard carbon negative electrode material of the present invention uses lignin-rich biomass material as raw material, and pre-calcines, acid-leaches, mixes with phenolic resin, calcines, and dries it. The auxiliary material is phenolic resin. During the calcination process, in the lattice formation stage, it will be impossible to form a completely identical unit cell structure due to impurities or uneven calcination temperature. Therefore, phenolic resin is used for filling. While providing carbon chains, phenolic groups are provided, which can better fill the gaps in the hard carbon layer, thereby improving the performance of the hard carbon negative electrode material.

[0049] In some embodiments, the biomass material includes at least one of palm shells, pollen, corn silk, peanut shells, and coconut shells. Preferably, the biomass material is palm shells. Due to the influence of lignin on the material, the richer the lignin, the better the performance of the hard carbon material. The lignin of younger palm trees is relatively sparse, while the lignin of older palm trees is relatively dense. After exploration, it was found that neither of them is suitable for making raw materials for hard carbon. The biomass material used in the present invention is palm shells that have been collectively planted for 3 to 5 years to ensure a stable and reliable source of raw materials.

[0050] In some embodiments, phenolic resin is added to the product after acid leaching, and calcination is specifically performed as follows:

[0051] adding phenolic resin to the acid-leached product to obtain a mixture;

[0052] The mixture is placed in a container and a porous aluminum plate is inserted into the mixture;

[0053] The container is placed in a calcining furnace, heated from room temperature to 1100-1220°C at 2-5°C / min, and kept at this temperature for 2-3 hours, and then cooled to room temperature at 1-2°C / min;

[0054] The mass of the phenolic resin is 2 to 8% of the mass of the product after acid leaching.

[0055] In the above embodiment, phenolic resin powder is added to the product after acid leaching, the mass of the phenolic resin is 2-8% of the mass of the product after acid leaching, and the mixture is fully mixed and filled into a container, for example, the container is a graphite box. Preferably, a porous aluminum plate is inserted into the graphite box. There are two main benefits of inserting the aluminum plate. 1. Because heat needs to be conducted, the material outside is often sintered and formed, and the temperature of the material inside has not yet reached the critical point. This will cause uneven heating of the internal material and cause defects in the material at the center of the graphite sagger. Therefore, inserting the aluminum plate can make the material conduct heat better. At the same time, the use of the porous aluminum plate can allow trace aluminum elements to be mixed into the negative electrode at a temperature of more than one thousand degrees. Aluminum-doped carbon powder can make the hard carbon conductivity reach 99.8% and the resistivity 0.4%.

[0056] In some embodiments, placing the precursor in an acid solution for acid leaching specifically comprises:

[0057] The precursor is crushed;

[0058] The crushed precursor is placed in an acid solution, heated to 45-55°C, stirred for 2-3 hours, aged for 2-3 hours, filtered to remove the supernatant, water is added to the precipitate for washing, and then sodium hydroxide is added to adjust the pH to neutral, and the solid product is filtered to obtain the product after acid leaching.

[0059] In some embodiments, the mass concentration of the acid solution is 20-40%;

[0060] In some embodiments, the acid solution includes at least one of a phosphoric acid solution, a sulfuric acid solution, and a nitric acid solution.

[0061] In the above embodiment, the precursor is placed in a double-roll mill for coarse crushing, and the crushed precursor is placed in a container for acid leaching. The pickling liquid is preferably a pickling liquid for the palm pre-burning. The pickling liquid is preferably a phosphoric acid solution with a mass concentration of 20-40%. Because the palm oil content is 5-8 times that of coconut shell, the use of phosphoric acid for heating and pickling can better thermally decompose and break the long chain; heat to 45-55°C, stir for 2-3h, age for 2-3h after stirring, filter out the supernatant, add clean water for rinsing five times, and then add a 10% mass concentration of sodium hydroxide solution to adjust the pH. At this time, the mixed solution is neutral, and the addition of sodium hydroxide can burn sodium into the hard carbon voids during the lower calcination, which can increase the battery discharge efficiency by 20%, and the pickling step is completed.

[0062] In some embodiments, pre-calcining the biomass material to obtain a precursor specifically comprises the following steps:

[0063] The biomass material is placed in a vacuum calcining furnace, calcined at 100-150°C for 30-50 minutes without oxygen, and then calcined at 180-250°C for 30-50 minutes without oxygen;

[0064] Inert gas is introduced into the vacuum calcining furnace, and the temperature is raised to 800-900°C, kept at this temperature for 1-2 hours, and cooled to room temperature to complete the pre-calcination.

[0065] In some embodiments, the biomass material is placed in a vacuum calcining furnace, the temperature is raised from room temperature to 100-150° C. at 1-2° C. / min, and calcined without oxygen for 30-50 min, and then the temperature is raised to 180-250° C. at 1-2° C. / min and calcined without oxygen for 30-50 min;

[0066] Inert gas is introduced into the vacuum calcining furnace, the temperature is raised to 800-900°C at 1-2°C / min, kept at this temperature for 1-2h, and cooled to room temperature at 1-2°C / min, thus completing the pre-calcination;

[0067] In the process of heating to 800-900°C at 1-2°C / min, the flow rate of the inert gas introduced is 30-60 mL / min; in the process of keeping the temperature for 1-2 hours, the flow rate of the inert gas introduced is 190-250 mL / min;

[0068] In some embodiments, the inert gas includes at least one of nitrogen, helium, argon, and neon.

[0069] In the above embodiment, a biomass material such as palm shell is placed in a vacuum calcining furnace, and the temperature is raised from room temperature to 100-150°C at 1-2°C / min, and calcined for 30-50min without oxygen. The main function of this stage is to remove free water in the biomass; then the temperature is raised to 180-250°C at 1-2°C / min and calcined for 30-50min without oxygen. This process mainly removes bound water in the biomass and performs preliminary carbonization; the air inlet valve of the vacuum calcining furnace is opened, and an inert gas is introduced for protection. After washing three times, the inert gas is continuously introduced, and the gas flow rate of the ventilation is 30-60mL / min, and the gas flow rate of the ventilation is 1-20mL / min. The temperature is raised to 800-900°C at 2°C / min, and kept warm for 1-2h; preferably, the speed of introducing the protective gas is increased during the insulation period and adjusted to 190-250mL / min. This preferred step can allow the tar and the like generated during the carbonization of lignin at this temperature to be quickly taken away by the gas, thereby reducing the content of organic impurities in the precursor; finally, the temperature is cooled to room temperature at 1-2°C / min, and the material is taken out to obtain a precursor. The above steps are the stages most likely to form ash. Cooling at this stage instead of transferring to the lattice formation temperature and transferring to the pickling stage can effectively remove the ash content in the product without affecting the final product structure.

[0070] In some embodiments, phenolic resin is added to the product after acid leaching, calcined, washed with water, and dried to obtain a hard carbon negative electrode material:

[0071] The calcined product is added to water, heated to 45-55° C., stirred for 2-3 hours, filtered and dried to obtain a hard carbon negative electrode material.

[0072] Specifically, the calcined product is added to water, heated to 45-55°C, stirred for 2-3 hours, filtered, and dried in a forced air drying oven at 80-100°C to obtain refined hard carbon. After crushing, the product is sieved using a 600-mesh sieve. The sieved material is a fine hard carbon material with good processing performance and excellent electrochemical performance. The mass ratio of the calcined product to water is (1-2):(2-5).

[0073] The present invention uses biomass such as palm as raw material, and prepares hard carbon anode material through pre-carbonization, acid washing and impurity removal, high-temperature carbonization, crushing and screening; electron microscope research shows that the prepared hard carbon has a porous interconnected network structure; X-ray diffraction and Raman spectroscopy analysis show that the carbonized material has a disordered structure and a large interlayer spacing (0.37nm); electrochemical research shows that 800°C pyrolysis of lignin in palm has good permeability and can provide 420mAh / g and 360mAh / g initial discharge and charging capacity; the sepals of palm (biowaste) produce hard carbon materials at a moderate carbonization temperature, with optimal microstructural properties and large interlayer spacing. These properties are responsible for its good electrochemical performance as an anode material for NIB (sodium ion battery). At present, biomass hard carbon materials are used in sodium ion batteries, and the main treatment methods are high-temperature pyrolysis and heteroatom doping. However, high-temperature pyrolysis has the problem that tar separation cannot be complete, and if heteroatom doping is used, the purity of hard carbon is not high, and other useless groups will be introduced. Therefore, the present invention has developed a set of effective hard carbon production technologies that can be industrialized in batches. It can prepare hard carbon negative electrode materials from palm waste, avoid the problem of tar separation that cannot be completely separated during high-temperature pyrolysis, and the problem of low purity of hard carbon due to heteroatom doping, and will not introduce other useless groups.

[0074] Based on the same inventive concept, the present invention also provides an application of the hard carbon negative electrode material prepared by the above-mentioned preparation method in the preparation of sodium ion batteries.

[0075] Based on the same inventive concept, the present invention also provides a sodium ion battery, comprising the hard carbon negative electrode material prepared by the above preparation method.

[0076] The following further illustrates the preparation method and application of the hard carbon negative electrode material and the sodium ion battery of the present application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as a limitation on the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0077] Example 1

[0078] The present invention provides a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0079] S1. Take palm shells grown collectively for 3 to 5 years, place the palm shells in a vacuum calcining furnace, raise the temperature from room temperature to 120°C at a rate of 1°C / min, and calcine without oxygen for 30 minutes, then raise the temperature to 220°C at a rate of 1°C / min and calcine without oxygen for 40 minutes;

[0080] Inert gas (specifically nitrogen) is introduced into a vacuum calcining furnace, the temperature is raised to 850°C at 1°C / min, kept at this temperature for 1h, and cooled to room temperature at 1°C / min, thus completing the pre-calcination to obtain a precursor;

[0081] In the process of heating to 850°C at a rate of 1°C / min, the inert gas flow rate was 40 mL / min; in the process of keeping the temperature for 1 hour, the inert gas flow rate was 220 mL / min;

[0082] S2, crushing the precursor;

[0083] The crushed precursor is placed in a 30% by mass phosphoric acid solution, heated to 40°C, stirred for 2 hours, aged for 2 hours, filtered to remove the supernatant, water is added to the precipitate for washing, and then sodium hydroxide is added to adjust the pH to neutral, and the solid product is filtered to obtain the product after acid leaching;

[0084] S3, adding phenolic resin to the acid-leached product to obtain a mixture; the mass of the phenolic resin is 6% of the mass of the acid-leached product;

[0085] The mixture is placed in a graphite box, and a porous aluminum plate is inserted into the mixture;

[0086] Place the graphite box in a calcining furnace, heat it from room temperature to 1160°C at 3°C / min, keep it at that temperature for 2h, and then cool it to room temperature at 1°C / min;

[0087] S4. Add the calcined product in S3 into water, heat to 50°C, stir for 2h, filter, and dry in a 100°C forced air drying oven to obtain refined hard carbon. After crushing, sieve with a 600-mesh sieve to obtain a hard carbon negative electrode material; the mass ratio of the calcined product to water is 1:3.

[0088] Performance Characterization

[0089] Figure 1 This is the XRD spectrum of the hard carbon negative electrode material prepared in Example 1.

[0090] from Figure 1 It can be seen from the figure that the hard carbon negative electrode material is an amorphous material, and from the XRD diagram it can be seen that the prepared material is a hard carbon negative electrode material.

[0091] Figures 2 to 5 These are SEM images of the hard carbon negative electrode material prepared in Example 1 at different magnifications.

[0092] from Figures 2 to 5 It can be seen that the prepared hard carbon negative electrode material is an amorphous material.

[0093] A hard carbon negative electrode material was prepared according to the method in Example 1. 0.1017 g of the prepared hard carbon negative electrode material was taken, the volume was fixed to 25 mL with water, and the content of Hg and other elements therein was tested. The results are shown in Table 1 below.

[0094] Table 1-Contents of elements in hard carbon negative electrode materials

[0095]

[0096]

[0097] Table 1 is the ICP test of the hard carbon negative electrode material. It can be seen from Table 1 that the purity of the hard carbon negative electrode material prepared by the present invention can reach 99.9%, the material consistency is good, and the purity is high.

[0098] The hard carbon negative electrode material prepared in Example 1 is assembled. The hard carbon negative electrode material, conductive carbon black and sodium carboxymethylcellulose (CMC) prepared in S3 are added with N-methylpyrrolidone (NMP) aqueous binder (SBR) and mixed evenly. The mixture is continuously stirred in a high-speed pulping machine to obtain a slurry. The slurry is evenly coated on a copper foil and placed in a vacuum drying oven at 100°C for 12 hours. Finally, the hard carbon negative electrode sheet is obtained by rolling and punching. The sodium metal sheet is used as the counter electrode, the polypropylene-based three-layer film is used as the diaphragm, and the 1MNaPF6 / EC+DEC+EMC (volume ratio is 1:1:1) solution is used as the electrolyte. The sodium ion battery is assembled in a glove box filled with argon and with a strictly controlled water and oxygen index. The sodium ion charge and discharge performance is tested, and the results are as follows: Figure 6 shown.

[0099] Figure 6 The first charge-discharge curve and the second charge-discharge curve are shown in FIG. 1 (the second charge curve overlaps with the first charge curve in the figure, which shows that the battery assembled with the hard carbon negative electrode material of the present invention has good consistency). Figure 6 It can be seen that the first charge and discharge capacity is 420mAh / g, and the first charge capacity is 360mAh / g.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material, characterized in that: The following steps are involved: Precalcining the biomass material to obtain a precursor; placing the precursor in an acid solution for acid leaching; Phenolic resin is added to the product after acid leaching, calcined, washed with water, and dried to obtain a hard carbon negative electrode material.

2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The biomass material includes at least one of palm shells, pollen, corn silk, peanut shells, and coconut shells.

3. The method for preparing the hard carbon negative electrode material according to claim 1, characterized in that: Phenolic resin is added to the product after acid leaching, and calcination is specifically as follows: adding phenolic resin to the acid-leached product to obtain a mixture; The mixture is placed in a container and a porous aluminum plate is inserted into the mixture; The container is placed in a calcining furnace, heated from room temperature to 1100-1220°C at 2-5°C / min, and kept at this temperature for 2-3 hours, and then cooled to room temperature at 1-2°C / min; The mass of the phenolic resin is 2-8% of the mass of the product after acid leaching.

4. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: Placing the precursor in an acid solution for acid leaching is specifically as follows: The precursor is crushed; The crushed precursor is placed in an acid solution, heated to 45-55°C, stirred for 2-3 hours, aged for 2-3 hours, filtered to remove the supernatant, water is added to the precipitate for washing, and then sodium hydroxide is added to adjust the pH to neutral, and the solid product is filtered to obtain the product after acid leaching.

5. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: Precalcining the biomass material to obtain a precursor specifically comprises the following steps: The biomass material is placed in a vacuum calcining furnace, calcined at 100-150°C for 30-50 minutes without oxygen, and then calcined at 180-250°C for 30-50 minutes without oxygen; Inert gas is introduced into the vacuum calcining furnace, and the temperature is raised to 800-900°C, kept at this temperature for 1-2 hours, and cooled to room temperature to complete the pre-calcination.

6. The method for preparing a hard carbon negative electrode material according to claim 5, characterized in that: The biomass material is placed in a vacuum calcining furnace, and the temperature is raised from room temperature to 100-150°C at 1-2°C / min, and calcined for 30-50min without oxygen, and then the temperature is raised to 180-250°C at 1-2°C / min, and calcined for 30-50min without oxygen; Inert gas is introduced into the vacuum calcining furnace, the temperature is raised to 800-900°C at 1-2°C / min, kept at this temperature for 1-2h, and cooled to room temperature at 1-2°C / min, thus completing the pre-calcination; In the process of heating to 800-900°C at 1-2°C / min, the flow rate of the inert gas introduced is 30-60 mL / min; in the process of keeping the temperature for 1-2 hours, the flow rate of the inert gas introduced is 190-250 mL / min; The inert gas includes at least one of nitrogen, helium, argon and neon.

7. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The mass concentration of the acid solution is 20-40%; The acid solution includes at least one of a phosphoric acid solution, a sulfuric acid solution, and a nitric acid solution.

8. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: Phenolic resin is added to the product after acid leaching, calcined, washed with water, and dried to obtain a hard carbon negative electrode material: The calcined product is added to water, heated to 45-55° C., stirred for 2-3 hours, filtered and dried to obtain a hard carbon negative electrode material.

9. Use of a hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8 in preparing a sodium ion battery.

10. A sodium ion battery, characterized in that: It comprises a hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Palm-based sodium ion battery hard carbon negative electrode material and preparation method thereof

    CN117080410A

  • Palm fruit shell derived hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN117623276A

  • Preparation method and application of biomass hard carbon negative electrode material with reduced pH value

    CN117923464A

  • Sodium-ion battery negative electrode biomass hard carbon material, preparation method and sodium-ion battery

    CN118529711A